User perspective on receiving adaptive equipment after stroke: A mixed-methods study. (October 2018) - Boland, Pauline; Levack, William M. M.; Graham, Fiona P.; Perry, Meredith A.
Background: Adaptive equipment (AE) is frequently provided during stroke rehabilitation by occupational therapists. Purpose: This study aimed to identify the AE that people typically use after a stroke and the outcomes achieved as a result, and to explore people's experiences obtaining and using AE, to inform both practice and policy in this field. Method: A mixed-methods study, involving a postal questionnaire and interviews, used descriptive statistics and grounded theory to analyze the quantitative and qualitative data, respectively. Findings: Questionnaire data ( n = 258) revealed mobility AE was issued most frequently, with increased safety as the primary reported outcome. Interview data ( n = 15) indicated relationships with health professionals and the hospital environment shaped early AE selection and use. Once home, making sense of AE and community participation were more influential. Implications: Therapeutic relationships and reflection time are critical to maximize AE use after stroke. Policy and related funding for AE need to prioritize community participation.